2015
DOI: 10.1074/jbc.r114.626820
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Aspects of Folded Protein Transport by the Twin Arginine Translocase (Tat)

Abstract: The twin arginine translocase (Tat) transports folded proteins of widely varying size across ionically tight membranes with only 2-3 components of machinery and the proton motive force. Tat operates by a cycle in which the receptor complex combines with the pore-forming component to assemble a new translocase for each substrate. Recent data on component and substrate organization in the receptor complex and on the structure of the pore complex inform models for translocase assembly and translocation. A translo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
88
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(92 citation statements)
references
References 83 publications
(164 reference statements)
2
88
0
Order By: Relevance
“…Because we found TatE cross-linked to TatC, it might also affect the way in which TatA and/or TatB associate with TatC. Common binding sites of TatA and TatB on TatC have recently been demonstrated, and it has been suggested that TatB might control the access and oligomerization of TatA on the inside of concentric TatBC assemblies (6,15,17). As we have shown here, TatE, at high concentrations, seems to be able to displace TatA from TatC.…”
Section: Cross-links Between Tatamentioning
confidence: 55%
See 2 more Smart Citations
“…Because we found TatE cross-linked to TatC, it might also affect the way in which TatA and/or TatB associate with TatC. Common binding sites of TatA and TatB on TatC have recently been demonstrated, and it has been suggested that TatB might control the access and oligomerization of TatA on the inside of concentric TatBC assemblies (6,15,17). As we have shown here, TatE, at high concentrations, seems to be able to displace TatA from TatC.…”
Section: Cross-links Between Tatamentioning
confidence: 55%
“…In cells overexpressing TatE-GFP, the major TatE-immunoreactive material had the expected molecular mass of the TatE-GFP fusion (approximately 37 kDa; Fig. 2A, lanes [3][4][5][6]. Expression of TatE-GFP did not noticeably influence the amount of the 9-kDa TatE band, demonstrating stability of the TatE-GFP construct.…”
Section: Substrate-dependent Relocation Of Tate From a Uniform Distrimentioning
confidence: 90%
See 1 more Smart Citation
“…TatA is a key component of the Tat system and considered to locally weaken the membrane, thereby -in conjunction with the other Tat system components -allowing the passage of folded proteins (19,18). TatA is anchored by its Nterminus in the cytoplasmic membrane (20).…”
Section: A Cell-growth Effect Of the Tata Membrane-anchor That Is Commentioning
confidence: 99%
“…The twin-arginine protein translocation (Tat) pathway operates in parallel to the Sec pathway to transport folded proteins across the prokaryotic cytoplasmic membrane and the thylakoid membrane of plant chloroplasts (10,11). Proteins are targeted to the Tat pathway by N-terminal signal peptides that contain a conserved twin arginine motif at the n-region/h-region boundary (12,13) (Fig.…”
mentioning
confidence: 99%